1998
DOI: 10.1007/s002030050558
|View full text |Cite
|
Sign up to set email alerts
|

New roles for CO 2 in the microbial metabolism of aliphatic epoxides and ketones

Abstract: Short-chain aliphatic epoxides and ketones are two classes of toxic organic compounds formed biogenically and anthropogenically. In spite of their toxicity, these compounds are utilized as primary carbon and energy sources or are generated as intermediate metabolites in the metabolism of other compounds (e.g., alkenes, alkanes, and secondary alcohols) by a number of diverse bacteria. One bacterium capable of using both classes of compounds is the gram-negative aerobe Xanthobacter strain Py2. Studies of epoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…Functionalization of inert substrates. The introduction of a carboxylic group is a common strategy in the assimilation of substrates that lack any functionalizable terminal carbon group, such as phenol, acetophenone, epoxypropane, or acetone (39,55,70,106) (Fig. 3).…”
Section: Carboxylases In Assimilatory Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalization of inert substrates. The introduction of a carboxylic group is a common strategy in the assimilation of substrates that lack any functionalizable terminal carbon group, such as phenol, acetophenone, epoxypropane, or acetone (39,55,70,106) (Fig. 3).…”
Section: Carboxylases In Assimilatory Pathwaysmentioning
confidence: 99%
“…Anaerobic metabolism of acetophenone in Aromatoleum aromaticum requires acetophenone carboxylase, which yields benzoylacetate (70). Epoxypropane and acetone are transformed into acetoacetate by NADPH:2-ketopropyl-CoM carboxylase/oxidoreductase (Xanthobacter autotrophicus Py2) and acetone carboxylase (Rhodobacter capsulatus), respectively (38,39). Subsequently, all these carboxylic acids are activated to their corresponding CoA-esters and further converted to central metabolites.…”
Section: Carboxylases In Assimilatory Pathwaysmentioning
confidence: 99%
“…When acetone consumption was examined in the absence of 2-propanol, a slow rate of consumption [9 nmol min-' (mg protein)-'] was observed. Recently, Ensign and coworkers (Ensign et al, 1998) demonstrated that for some bacteria the first step in the metabolism of ketones involves a carboxylation reaction. For example, the consumption of acetone by resting cells of Xanthobacter Py2 was stimulated by addition of CO, (Sluis et al, 1996).…”
Section: Alcohol Consumption By Butane-grown 'P Butanovora 'mentioning
confidence: 99%
“…The PCM described in this study is derived from X. autotrophicus strain Py2, a facultative aerobe that was first isolated from black pool sludge, has versatile metabolic capabilities, and is able to utilize 2-hydroxyisobutyric acid, propene, and trichloroethylene, 1-butene among others, as carbon sources (31). The large subunit of PCM has Leu and Asn residues that are also seen in other genes annotated as being MCM-like in the database (Fig.…”
Section: Discussionmentioning
confidence: 99%